Neogene basins in Eastern Rif of Morocco and their potential to host native sulphur. Issue 1 (31st December 2022) - Boubkari, Laila; Achalhi, Mohammed; Raji, Otmane; Ouabid, Muhammad; Bodinier, Jean-Louis; El Kati, Imad; El Messbahi, Hicham
ABSTRACT: Sediment-hosted sulphur deposits provide valuable information on sedimentary biogeochemical processes related to microbial activity and are paleoenvironmental proxy records. They are also used as markers for oil exploration and the largest ones may represent exploitable economic resources of sulphur. Biogenic sulphur occurrences associated with Neogene formations are found around the Western Mediterranean, in Southern Europe (e.g. Hellin, Lorca, and Teruel, Spain, and Sicily, Italy). In northern Morocco, similar geological settings are present where several sediment-hosted sulphur occurrences were reported by unpublished studies. In this study, we provide the first description of such occurrences selected from two Neogene basins in the Eastern Rif (Taza-Guercif and Boudinar) and studied using sedimentological facies analysis and mineralogical data. The studied facies occur as yellowish sub-spherical concretions, nodules, and laminated structures associated with gypsiferous marls or organic-matter-rich marly clays and gypsum lenses. Mineralogical analysis revealed a mineralogical assemblage composed mainly jarosite, gypsum, and native sulphur. These geo-markers are indicative of bacterially mediated sulphate reduction and favourable conditions for the formation of sulphur, especially at the level of the Guercif basin. In contrast, Ras Tarf volcanism probably contributed to the observed facies in the Boudinar basin through different processes.